Long-term clinical outcomes of endoscopic retrograde cholangiopancreatography for pancreatic duct stone treatment in children with chronic pancreatitis - Yong Lv; Fangdi Yu; Bo Xiang (PLoS ONE, 2026)
Background Evidence on long-term outcomes of endoscopic retrograde cholangiopancreatography (ERCP) for pancreatic duct stones (PDS) in children with chronic pancreatitis (CP) remains scarce. This study aimed to evaluate the long-term clinical outcomes of ERCP in this population. Methods A single-center retrospective cohort study was conducted on children with CP and PDS who underwent ERCP at our Hospital (2008.1.1–2024.12.31). Follow-up assessed stone clearance, complications, pain relief, pain type, growth, quality of life (QoL), and long-term complications. Results A total of 90 children with CP and PDS were enrolled in this single-center retrospective cohort study. ERCP achieved 72.1% complete stone clearance; overall complications were 9.6%. Among the 90 patients, 77 (85.6%) completed the full follow-up. Post-ERCP, all abdominal pain subtypes significantly decreased (P < 0.001), with 70.1% complete pain relief. Height and weight increased (P < 0.01); QoL (PedsQL™4.0) scores rose from 69 to 85 points (P < 0.001). Long-term complications included new diabetes (5.2%) and steatorrhea (5.2%); PDS recurrence was 7.8%. Conclusion ERCP is safe and effective for children with CP and PDS, significantly improving long-term pain, growth, and QoL, supporting its role as a first-line therapy.